Effect of Different Types of Shoes on Lower Limb Muscular Activation during Walking in Women - Kang, Bo-Ra; Her, Jin-Gang; Woo, Ji-Hea; Kim, Hee-Soo; Chung, Sin-Ho (International Journal of Innovative Research in Medical Science, 2019)
Purpose: The present study intended to compare the effects on the female body of high-heeled shoe types, including regular high heels, wedge heels, and platform heels, with those of sneakers during level walking by examining muscular activity in the lower limbs. Materials and Methods: Participants were 20 women in their 20s or 30s who regularly wear different types of size 8 (US size). The heel height tested was 7 cm, and electromyographic muscular activation (% maximal voluntary isometric contraction) was measured in the rectus femoris, tibialis anterior, and semitendinosus muscles of participants’ dominant legs during walking 15 m at a self–selected walking velocity step speed. Results: Rectus femoris revealed significant electromyographic differences among shoe types in terms of muscular activation (p = .013). Multiple comparisons among shoe types and activation of various muscles were carried out. These showed significant (p < .05) differences in rectus femoris muscular activation among shoe types, most notably between sneakers and platform heels (average -15.69 (SD = 4.22) (p = .002)) and between sneakers and high heels (average 13.83 (SD = 4.22) (p = .010)). Conclusion: Results obtained revealed significant variation in muscular activation of rectus femoris among shoe types. Multiple pairwise comparisons of the differences in muscular activation of rectus femoris revealed significant differences between sneakers and high heeled shoes and between sneakers and platform heels. Therefore, the results of the present study are expected to be beneficial for ordinary individuals in selecting appropriate types of shoes that reduce the level of the muscle activation.